The Impact of social responsibility towards human resources in achieving Organizational Excellence case study of Regional Center for Medical Imaging, Laghouat. Algeria - Halmous, Messaouda (Dirassat Journal Economic Issue, 2020)
The company’s concerns in the past used to be confined to the economic goal for which it had been founded, namely to make a profit, while ignoring its social responsibility. However, this narrow view expanded to go so far as to confirm that the company includes the various social practices it carries out towards the society in general and its human resources in particular. Based on this standpoint, we will try Through this paper, we will try to address various practices of social responsibility towards human resources, which are able to contribute organizational excellence While highlighting the Regional Center of Medical Imaging Laghouat. In order to achieve this aim, A questionnaire composed of (33) items and distributed into (3) domains, it was relied on the descriptive statistical method, and the use of the program (SPSS 22).the study confirmed a significant statistical impact of at the significance level (0.05) for the social responsibility towards human resources on achieving an organizational excellence.